Հայ փիլիսոփայության ձևավորման որոշ առանձնահատկությունների շուրջ. Դավիթ Անհաղթ - Ս. Ա. Սարգսյան-Կատվալյան (ՀՀ ԳԱԱ հրատ.)
Армянская философия сформировалась в V-VI вв. как общехристианская патристика-апологетика, в развитии которой значительную роль сыграли идеи Езника Кохбаци. Armenian philosophy was formed in the V-VI centuries as a common Christian-patristic apologetics, in the development of which the ideas of Yeznik of Kolb have played major role.
Keywords: B Philosophy; Psychology; Religion; B Philosophy